Peranan Bahasa Inggris dalam Meningkatkan Kompetensi Komunikasi Mahasiswa Sastra Inggris - Nadia Destyana; Ratesya Septiana Hidarusman; Zidane Reandra; Sri Mulyeni (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This research focuses on comprehensive analysis of the crucial role of English proficiency as a vital instrument in enhancing the holistic communication competence of English Literature students amdist the dynamics of globalization. Utilizing a literature study research method trough a systematic review of various scholarly references, academic journals, and empirical findings, this study evaluates interaction barries such as limited vocabulary, syntatic complexity, and psychological constraints including low self confidence. The findjngs demonstrate that proficient language mastery is directly proportional to the improvement of critical literary work analysis and active participation in broader academic discourse. Furthermore, this study confirms that the implementation of interactive active learning methodologies such as role playing, thematic debates, and collaborative presentations integrated with cutting edge technology acts as a primary catalyst. These strategies not only mitigate communicative barriers but also substantially enhance self directed learning efficiency and career readiness in multilingual professional environment. Ultimately, this research offers a new theoretical contribution to higher education curriculum roadmaps that are more adaptive, responsive, and outcome oriented for learners domestically and internationally. Through this approach, educational institutions are expected to produce competitive graduates ready to face the dynamic challenges of the rapidly evolving global stage.